Commande sans capteur de vitesse d’une génératrice asynchrone à double alimentation Associée à un Observateur Adaptatif - عائشة, الاسود; حنان, مسعودي (University Of El Oued, 2020)
This work is devoted the sensorless vector control of active and reactive energy of a doubly fed induction machine (DFIM) by adaptive observers integrated in wind power system. The power transfer between the stator and the network is achieved by acting on the rotor signals by bidirectional converter, the performance and robustness are analyzed and compared by simulation based on software Matlab / Simulink. يقدم هذا العمل التحكم النشط النشط والمتفاعل للطاقة دون مستشعر ميكانيكي باستخدام مراقب تكيفي لماكينة طاقة ثنائية غير متزامنة (Mada) مدمجة في نظام الرياح. يتم نقل الطاقة بين العضو الساكن والشبكة عن طريق العمل على الإشارات الكهربية عبر محول ثنائي الاتجاه. يتم تحليل الأداء والقوة ومقارنتهما باستخدام المحاكاة باستخدام برنامج MATLAB/Simulink.
Machine éléctrique مذكرة ماستر تخصص
Keywords: Key words: Wind System, sensorless control, adaptive observers, doubly fed induction generators. MPPT.; الكلمات الأساسية: نظام الرياح، التحكم من دون مستشعر، المراقبين المتكيفة، المولد غير المتزامن مزدوج الطاقة، MPPT.